Hydrophobic/hydrophilic P(VDF-TrFE)/PHEA polymer blend membranes - Tamaño-Machiavello, M. N. (2016)
Polymer blend membranes have been obtained consisting of a hydrophilic and a hydrophobic polymers distributed in co-continuous phases. In order to obtain stable membranes in aqueous environments, the hydrophilic phase is formed by a poly(hydrohyethyl acrylate), PHEA, network while the hydrophobic phase is formed by poly(vinylidene fluoride-co-trifluoroethylene) P(VDF-TrFE). To obtain the composites, in a first stage, P(VDF-TrFE) is blended with poly(ethylene oxyde) (PEO), the latter used as sacrificial porogen. P(VDF-TrFE)/PEO blend membranes were prepared by solvent casting at 70° followed by cooling to room temperature. Then PEO is removed from the membrane by immersion in water obtaining a P(VDF-TrFE) porous membrane. After removing of the PEO polymer, a P(VDF-TrFE) membrane results in which pores are collapsed. Nevertheless the pores reopen when a mixture of hydroxethyl acrylate (HEA) monomer, ethyleneglycol dimethacrylate (as crosslinker) and ethanol (as diluent) is absorbed in the membrane and subsequent polymerization yields hybrid hydrophilic/hydrophobic membranes with controlled porosity. The membranes are thus suitable for lithium-ion battery separator membranes and/or biostable supports for cell culture in biomedical applications.